THE EFFECTS OF COHESIVENESS ON THE PERSUASIVENESS AND PERSUASIBILITY OF INDIVIDUALS IN TWO PERSON-GROUPS - Schwartz, Fred S. (My University, 1969)
The present study is concerned with the effects of different levels of "cohesiveness" on the persuasiveness an persuasibility of individuals in a two person verbal interaction situation. In particular, changes in verbal behaviour over time are obtained. Now the sex of the participants affects the discussion and outcome is also investigated. The results indicated that the favorability predisposed subjects are more persuasible than unfavorably predisposed subjects. Further, male subjects speak more than female subjects and this is reflected in the number of positive, negative and neutral statements they emit. Overall decreases in the emission of positive statements and over-all increases in the emission of negative statements were found to accompany opinion change.
COHESIVENESS AS A DETERMINANT OF PERSUASIVENESS AND PERSUASIBILITY
Keywords: Cohesiveness; Persuasibility; Agreeableness; Social Behaviour; Face-to-Face interaction